Mengoptimalkan Pertumbuhan UMKM Melalui Pendampingan Dan Penyelenggaran Posko Pembuatan NIB Di Kelurahan Klampok Kota Blitar (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic growth and community welfare. Observation is carried out through three methods, namely: (1) conducting interviews, (2) documenting, and (3) direct field visits. From the results of these observations, several common issues faced by MSMEs are identified, such as unclear MSME status, marketing challenges, and difficulties in establishing the business identity for these enterprises. MSMEs are resilient in any situation and provide employment opportunities, reduce unemployment, and significantly contribute to the economy. Enhancing product and service innovation, human resources development, technology, and market expansion are challenges that MSMEs must face in the global competition. Business legality, including the Business Identification Number (NIB), is crucial to ensure the security and safety of the business. NIB replaces previous permits and offers many benefits for long-term business management. Electronic licensing systems, such as the Online Single Submission (OSS), facilitate permit management and provide certainty for business operators. In the city of Blitar, MSMEs play a vital role in the local economy, particularly in the agricultural sector. Adequate infrastructure and supporting facilities further boost the development of MSMEs in Blitar. However, MSMEs in Klampok Subdistrict still face challenges in registering NIB, such as a lack of technological understanding and bureaucratic complexity. Through mapping, counseling, and NIB registration assistance centers, MSME operators in Klampok Subdistrict can overcome these issues. This mentoring activity enhances the knowledge of Klampok residents about the importance of entrepreneurship, business development, and the benefits of business legality. With the NIB, MSME operators can apply for funding assistance to develop their businesses.